First Mode Damping Ratios for Buildings. Issue 1 (February 2015) - Bernal, Dionisio; Döhler, Michael; Kojidi, Salma Mozaffari; Kwan, Kenny; Liu, Yang
Expressions for the expected value of the first mode damping ratio are derived by using 122 seismic responses from concrete buildings and 81 from steel. The results include dissipation at the soil-structure interface and are appropriate for situations in which this source of dissipation is not included in the model. Comparisons between models of different complexity indicate the appropriateness of using a single regressor, for which the building height is used. It is shown that the Fisher information about damping increases with the number of response cycles; this result is used to define weights for the residuals of the regression. The effective damping in steel buildings, with the exception of very tall structures, is found to be larger than the 2% typically used in practice, whereas the 5% assigned to concrete proves to be similar to the mean of the data set.